2023
DOI: 10.1186/s42836-022-00159-y
|View full text |Cite
|
Sign up to set email alerts
|

A low dislocation rate after revision total hip arthroplasty performed through the anterior approach

Abstract: Background Dislocation is a major complication in revision total hip arthroplasties. This study aimed to evaluate the dislocation rate, complications, and functional scores of revision total hip arthroplasty performed through the direct anterior approach. Methods Between January 2014 and March 2020, 84 patients undergoing revision total hip arthroplasty were retrospectively reviewed. All operations were performed through the direct anterior approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Early rates of THA failure have been reportedly increasing ranging from 24% to 50% within 5 years of the surgery due to femoral or acetabular prosthetic fracture, mal-alignment, or instability [ 19 - 21 ]. A study reported early femoral periprosthetic fractures and loosening were significantly higher in the DAA when compared to the LA and PA. Additionally, early femoral component loosening was higher with DAA than LA and PA [ 19 , 22 ]. Malalignment of the acetabular cup causes impingement, dislocation, and loosening of the acetabular component [ 23 ].…”
Section: Approaches In Total Hip Arthroplastymentioning
confidence: 99%
“…Early rates of THA failure have been reportedly increasing ranging from 24% to 50% within 5 years of the surgery due to femoral or acetabular prosthetic fracture, mal-alignment, or instability [ 19 - 21 ]. A study reported early femoral periprosthetic fractures and loosening were significantly higher in the DAA when compared to the LA and PA. Additionally, early femoral component loosening was higher with DAA than LA and PA [ 19 , 22 ]. Malalignment of the acetabular cup causes impingement, dislocation, and loosening of the acetabular component [ 23 ].…”
Section: Approaches In Total Hip Arthroplastymentioning
confidence: 99%